2018
DOI: 10.1097/mlr.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Culture Change Practice in US Nursing Homes

Abstract: Background and Objectives: Given the dynamic nursing home (NH) industry and evolving regulatory environment, depiction of contemporary NH culture-change (person/resident-centered) care practice is of interest. Thus, we aimed to portray the 2016/17 prevalence of NH culture change-related processes and structures and to identify factors associated with greater practice prevalence. Research Design and Methods: We administered a nationwide survey to 2,142 NH Administrators (NHA) at NHs previously responding to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…Our finding that investment by senior management is linked with successful outcomes is consistent with prior research identifying associations between leadership and the adoption of change ( Castle & Decker, 2011 ; Corazzini et al, 2015 ; Donoghue & Castle, 2009 ). Although the measurement in this study focused specifically on leadership’s willingness to invest resources in the adoption and implementation of a new clinical model, it is likely that this is associated with high-quality leadership characteristics that facilitate culture change, such as open communication, shared decision-making, staff education, and a focus on positive leadership–staff relationships ( Miller et al, 2018 ). In a prior qualitative study of barriers to implementation of OPTIMISTIC, we found that miscommunication was a major barrier to implementation which often resulted in a lack of knowledge about both the OPTIMISTIC program and how to interact with program staff ( Ersek, Hickman, Thomas, Bernard, & Unroe, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that investment by senior management is linked with successful outcomes is consistent with prior research identifying associations between leadership and the adoption of change ( Castle & Decker, 2011 ; Corazzini et al, 2015 ; Donoghue & Castle, 2009 ). Although the measurement in this study focused specifically on leadership’s willingness to invest resources in the adoption and implementation of a new clinical model, it is likely that this is associated with high-quality leadership characteristics that facilitate culture change, such as open communication, shared decision-making, staff education, and a focus on positive leadership–staff relationships ( Miller et al, 2018 ). In a prior qualitative study of barriers to implementation of OPTIMISTIC, we found that miscommunication was a major barrier to implementation which often resulted in a lack of knowledge about both the OPTIMISTIC program and how to interact with program staff ( Ersek, Hickman, Thomas, Bernard, & Unroe, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of culture change practices in Minnesota NHs was comparable to that of a national representative sample of NHs (Miller et al, 2018), wherein culture change practices associated with resident-centered care, physical environment transformation, and end-of-life care were more frequently implemented than practices associated with staff empowerment, staff leadership, and family and community engagement. This study, looking beyond individual culture change domains, integrated the multidimensional measures of culture change practices to identify an empirical typology of culture change implementation.…”
Section: Discussionmentioning
confidence: 77%
“…Items in the domain of physical environment were measured using a two-level Likert-type scale (0-1), and items in other domains were measured using a three-level Likert-type scale (0-2). As suggested by the previous use of the instrument (Miller et al, 2018), a composite score was obtained for each domain by summing the raw item scores, which were then rescaled to the range of 0 to 100. The missing value of an item was imputed using the mean of completed items in a given domain if one or two items were missing for that domain (imputations were performed for 1-11 NHs per domain).…”
Section: Study Variables and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in a national survey of culture change practices in U.S. NHs, culture change practices associated with resident-centered care and physical environment association were more prevalent than practices associated with staff empowerment and family and community engagement (Miller et al, 2014(Miller et al, , 2018. With the development of comprehensive domain-specific culture change assessment tools, deconstructing the complex culture change into its domains and evaluated domain-sensitive outcomes has become possible (Miller et al, 2014(Miller et al, , 2018. Examining domain-specific relationships will better inform the development of outcomeoriented culture change initiatives and maximize the efficacy and cost-effectiveness of culture change interventions (Miller et al, 2014(Miller et al, , 2018.…”
Section: Literature Reviewmentioning
confidence: 99%